PENDUGAAN BIOMASSA DAN KARBON TERSIMPAN MANGROVE Rhizopora apiculata DAN Sonneratia alba DI DESA SIMAU - Ronald K Lembang; Stenly Huliselan; Fifin Adji (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
Global warming is now a global issue marked by the increase of carbon dioxide content in the Earth's atmosphere, so that the impact of climate change can affect the ecological, social and economic aspects. The existence of forests is very important as a reducer of CO2 gas through photosynthesis process and can store carbon in the form of biomass, one of mangrove forest. This study aims to determine the total amount of biomass on surface and carbon stored in Rhizoporan apiculata mangrove and Sonneratia alba. The method used is a pathway method by creating a path along 100 meters and then dividing it in 10 x 10 meters randomly determined plots. Biomass estimation uses previously developed allometric equations in both types. The results showed that the biomass on surface contained in the Rhizopora apiculata type was 7.80 tons/ha and the total carbon deposit was 3.67 tons/ha, while in the Sonneratia alba type, the amount of surface biomass was 3.33 tons/ha and the total carbon storage of 1.5 tons / ha.